Experimental investigation on the seismic resistance of RC columns after acid rain corrosion - Lihua Niu; Shansuo Zheng; Junfeng Guan; Lielie Li; Haorui Xie; Shaohua Gao (Scientific Reports)
Abstract Acid rain can significantly undermine the structural integrity and seismic resilience of concrete structures, posing substantial risks of catastrophic failures and jeopardizing safety. However, studies on the seismic behavior of reinforced concrete (RC) columns affected by acid rain corrosion remain nascent. Therefore, this study explored the impact of acid-rain corrosion extent and axial compression ratio on the seismic behavior of RC columns that experienced flexural failure using an artificial rapid corrosion method and pseudo-static test in sequence. The corrosion-induced damage, weight loss of the reinforcement, failure pattern, hysteretic behavior, load-bearing capacity, deformation capacity, stiffness degradation, and energy dissipation were analyzed. The test observations showed that the acid rain corrosion extent was more pronounced in the column peripheries compared to their central sections. As the number of ARCCs (acid rain corrosion cycles) increased, the damage extent of column specimens was gradually aggravated; the load-bearing, deformation, and energy absorption capacities were significantly reduced. Notably, the column specimen RCZ-4 compared to RCZ-1, with reductions of 14.54% in peak load, 22.58% in plastic rotation, and 28.6% in total cumulative energy dissipation. As the axial compression ratio was increased from 0.3 to 0.5, the column specimens exhibited a 17.12% increase in peak load, alongside a decline in plastic rotation by 25.40% and a reduction in cumulative energy dissipation by 25.85%. Based on the experimental results and the existing theoretical, a calculation formula for the flexural failure skeleton curve characteristic point parameters of RC columns was proposed, considering the impact of acid rain corrosion damage and axial compression ratio. The proposed calculation method could effectively determine the load-bearing and deformation capacity of RC columns under low cyclic loading. The results of this study enable engineers to better understand the seismic behavior of RC columns in an acid rain corrosion environment.